Convenio 169 de la OIT sobre pueblos indígenas y tribales - Autores, Varios (2002)
The General Conference of the International Labor Organization: Convened in Geneva by the Governing Body of the International Labor Office and gathered in that city on June 7, 1989, at its seventy-sixth meeting; Observing the international standards set forth in the Convention and Recommendation on Indigenous and Tribal Populations, 1957.